Selected documents of the international petroleum industry. - Organization of Petroleum Exporting Countries (Vienna : Organization of the Petroleum Exporting Countries, 1968)
This volume is intended as the first in a series designed to gather in a single convenient reference all of the most important official documents published each year and having relevance for the international petroleum industry. These deals with information from exporting countries,, the foreign capital involved in the production of most oil exported in international trade among others.
usc 22/01/2019
Loans
Keywords: Petroleum industry and trade; Petroleum law and legislation